2021
DOI: 10.2337/dc20-3135
|View full text |Cite
|
Sign up to set email alerts
|

Racial, Rural, and Regional Disparities in Diabetes-Related Lower-Extremity Amputation Rates, 2009–2017

Abstract: To examine the racial/ethnic, rural-urban, and regional variations in the trends of diabetes-related lower-extremity amputations (LEAs) among hospitalized U.S. adults from 2009 to 2017. RESEARCH DESIGN AND METHODSWe used the National Inpatient Sample (NIS) (2009-2017) to identify trends in LEA rates among those primarily hospitalized for diabetes in the U.S. We conducted multivariable logistic regressions to identify individuals at risk for LEA based on race/ethnicity, census region location (North, Midwest, S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…A survey conducted in 2021 found that people living in urban areas were willing to travel, on average, 31.9 minutes to get routine care 48 . The 2017 National Household Travel Survey similarly found that people living in urban areas were willing to travel 25.5 minutes or 8.1 miles for medical care 103 . As a result, we can conclude that people in urban areas are willing to travel much more than 1 mile to get a healthcare service.…”
Section: Discussionmentioning
confidence: 99%
“…A survey conducted in 2021 found that people living in urban areas were willing to travel, on average, 31.9 minutes to get routine care 48 . The 2017 National Household Travel Survey similarly found that people living in urban areas were willing to travel 25.5 minutes or 8.1 miles for medical care 103 . As a result, we can conclude that people in urban areas are willing to travel much more than 1 mile to get a healthcare service.…”
Section: Discussionmentioning
confidence: 99%
“…Additional research to identify the best practices to close the gaps in health disparity for these populations should be prioritized. [20,21] A model such as that employed in this study, where wound-specialized APRNs can deliver timely and extensive interventions in the home setting, could be effective at closing this gap.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, a large longitudinal analysis on the National Inpatient Sample identified trends in LEAs rates in patients primarily hospitalized with diabetes in the US between 2009 and 2017. The Authors found an increasing annual incidence in LEAs across all racial/ethnic and rural/urban groups, which was primarily driven by increase of minor amputations – by roughly 87% from 2009 to 2017 – whereas major amputations increased by 42% ( 21 ). Interestingly, the odds of a major amputation were significantly higher (from 10 to 30% of increase) for Black, Native American and Hispanic ethnicities compared with White groups ( 21 ), with similar figures observed in the economically disadvantaged areas compared to more developed ones.…”
Section: Subsections Relevant For the Subjectmentioning
confidence: 98%
“…The Authors found an increasing annual incidence in LEAs across all racial/ethnic and rural/urban groups, which was primarily driven by increase of minor amputations – by roughly 87% from 2009 to 2017 – whereas major amputations increased by 42% ( 21 ). Interestingly, the odds of a major amputation were significantly higher (from 10 to 30% of increase) for Black, Native American and Hispanic ethnicities compared with White groups ( 21 ), with similar figures observed in the economically disadvantaged areas compared to more developed ones. These findings are consistent with other recent reports of disproportionately higher rates of LEAs and other diabetes-related complications among racial and ethnic minority populations ( 10 , 22 24 ).…”
Section: Subsections Relevant For the Subjectmentioning
confidence: 98%